Colonic epithelium is diffusely abnormal in ulcerative colitis and colorectal cancer. Issue 6 (June 1995) - Gibson, P; Rosella, O; Nov, R; Young, G
Abstract : The hypothesis that the colonic epithelium is diffusely abnormal in ulcerative colitis was examined by comparing disease related responses in expression of markers of differentiation by colonic crypt cells to culture with and without butyrate. Cells were isolated from patients with normal colon (15), cancer (24), ulcerative colitis (19), or Crohn's disease (16). Alkaline phosphatase activities were measured in cell homogenates and the rate of glycoprotein synthesis assessed at the end of 24 hours of culture and expressed relative to the rate of protein synthesis as the G:P ratio. Alkaline phosphatase activities, but not G:P ratios, differed across the groups before and after 24 hour culture (p < 0.05), activities being lowest in the cancer group and highest in inflammatory bowel disease groups. Butyrate (1 mM) suppressed alkaline phosphatase activities in the cancer group by mean (SEM) of 17 (4) (p = 0.006) compared with no change in the other groups. Butyrate suppressed G:P ratios only in the cancer (6 (3)%, p = 0.03) and ulcerative colitis groups (5 (3)%, p = 0.04) and the changes in both were different (p < 0.05) from those in normal cells (increase of 10 (7)%). Changes in ulcerative colitis were different from those in Crohn's disease (p = 0.029). Responses were independent of the presence or absence of mucosal inflammation. These data confirm the diffuse nature of epithelial abnormalities in colorectal cancer. In ulcerative colitis, a different pattern of abnormality occurs, supporting the notion that the epithelium is also diffusely abnormal independent of mucosal inflammation.